Methane-Induced Deformation of Porous Carbons: From Normal to High-Pressure Operating Conditions - Kowalczyk, Piotr; Furmaniak, S.; Gauden, P.; Terzyk, A. (American Chemical Society, 2012)
Applying developed recently thermodynamic model of adsorption-induced deformation of microporous carbons (Kowalczyk, P.; Ciach, A.; Neimark, A. Langmuir 2008, 24, 6603), we study the deformation of carbonaceous porous materials due to adsorption of methane at 313 K andpressures up to 19 MPa. The internal adsorption stress induced by adsorbed/compressed methane is very high in the smallest micropores (for instance, adsorption stress in 0.315 nm ultra-micropore reaches 1.8 GPa at 19 MPa). Model calculations show that depending on pore structure both monotonic (i.e.,expansion) and nonmonotonic (i.e., initial contraction and further expansion) methane stress-strain isotherm are theoretically predicted. Our calculations reproduce quantitatively the methane stress-strain isotherm on carbide-derived activated carbon at 313 K and experimental pressures up to 5.9 MPa. Moreover, we extrapolate methane stress-strain isotherm measured by the dilatometric method up to 19 MPa to mimic high pressure operating conditions. We predict that expansion of the studied carbon sample reaches 0.3% of volume at 19 MPa and 313 K. From our extrapolation of experimental dilatometric deformation data to high pressure conditions, we predict that the reduction of pressure from 19 to 1 MPa is accompanied by shrinkage of carbon sample by about 0.28% of volume. Comparison with recent study due to Yang et al. (Yang, K.; Lu, X.; Lin, Y.; Neimark, A. V. Energy Fuels 2010, 24, 5955-5964) shows that studied activated carbon is more resistant to adsorption stress than various coal samples. Presented study can be useful for optimization of operating conditions used in methane gas-extraction technologies.